Aphoric Utterance as a Language Model of Winged Words (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
Winged words were identified both as would-be and as objective language units that are contrasted as occasional and conventional. The main characteristics of winged words are language model and stability. Language model is determined by the formation of would-be winged word with the help of definite model of such language or speech units, which are characterized by stability (and / or reproducibility) of their structure. Stability is determined by the presence of unique link between all or the main would-be components of an winged word. This stability defines its reproducibility in speech (as a single quote or en-masse reproducible units) and its belonging to a particular type of free or stable units. The quality of language model and stability of would-be winged words are closely linked with each other, which provides high degree of recurrence by native speakers and en-masse reproduction in speech of each would-be winged word.The following main structural and semantic models of would-be winged words were found out: figurative word; non-figurative word; figurative combination of words; non-figurative combination of words; figurative expression; non-figurative expression; non-aphoristic figurative utterance; non-aphoristic non-figurative utterance; aphoristic figurative utterance; aphoristic non-figurative utterance. Each model has its own further differentiation according to the features of the structure and semantics, the degree of stability and idiomatic character, the implementation of poetic and rhetorical means and others. The model of aphoristic utterance has a very high degree of efficiency among other language models of would-be winged words. This fact is proved by the large quantitative index of its representation in the winged words stock in different languages (There are about 30% of aphoristic utterance in the winged words stock of the Modern Belarusian).
Keywords: Aphoric Utterance; Language Model; Winged Word; Modern Belarusian; Modern Russian